2020
DOI: 10.1037/abn0000512
|View full text |Cite
|
Sign up to set email alerts
|

The association between general childhood psychopathology and adolescent suicide attempt and self-harm: A prospective, population-based twin study.

Abstract: Few quantitative behavior genetic studies have examined why psychopathology is associated with suicide attempt (SA) and self-harm (SH) in adolescence. The present study analyzed data from the Child and Adolescent Twin Study in Sweden to examine the extent to which genetic and environmental factors explain SA/SH and its association with psychopathology in childhood, an often-cited risk factor of subsequent SA/SH. When children were 9 or 12 years old (n = 30,444), parents completed the Autism–Tics, AD/HD and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 77 publications
0
18
0
Order By: Relevance
“…We analyzed the SH/SA items separately and together (either SH or SA), consistent with prior research. 22…”
Section: Sh/samentioning
confidence: 99%
“…We analyzed the SH/SA items separately and together (either SH or SA), consistent with prior research. 22…”
Section: Sh/samentioning
confidence: 99%
“…A total of 17 full-text articles fulfilled the selection criteria on the genetics of adolescent suicide, including 7 family and 10 candidate gene association studies [17,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. Five of these association studies followed a case-control design [39,43,46,48,51], and one had a combined family and casecontrol design [37].…”
Section: Resultsmentioning
confidence: 99%
“…The results suggested that "effects of mental disorders on the risk of suicide attempt were exerted almost exclusively through a general psychopathology factor representing the shared effect across all mental disorders" (Hoertel et al, 2015, p. 718). A genetically-informed study among youth suggested that the association between a general psychopathology factor (not including gambling disorder) and suicide attempt was explained by overlapping genetic risk factors (O'Reilly et al, 2020). Taken together, these findings suggest that the genetic association between disordered gambling and suicidality among women is unlikely to be specific to disordered gambling, but rather nonspecific genetic risk factors that increase the general liability for developing a mental disorder.…”
Section: Biometric Twin Modeling Of Disordered Gambling and Suicidalitymentioning
confidence: 97%